2021
DOI: 10.3389/fcell.2021.649205
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Notch Signaling: From Cancer to Inflammatory Disorders

Abstract: Over the past two decades, the Notch signaling pathway has been investigated as a therapeutic target for the treatment of cancers, and more recently in the context of immune and inflammatory disorders. Notch is an evolutionary conserved pathway found in all metazoans that is critical for proper embryonic development and for the postnatal maintenance of selected tissues. Through cell-to-cell contacts, Notch orchestrates cell fate decisions and differentiation in non-hematopoietic and hematopoietic cell types, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 172 publications
(208 reference statements)
0
48
0
Order By: Relevance
“…As a result, medicines that block or promote NOTCH signaling may be particularly useful depending on the situation. For example, NOTCH inhibitors such GSI (Gamma-Secretase Inhibitor) and MK-0752 for solid tumors have been tested in Phase I clinical trials, resulting in stable disease [ 42 , 43 ]. EMT and tumor cells’ invasiveness in various malignancies were also enhanced by collagen-rich CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, medicines that block or promote NOTCH signaling may be particularly useful depending on the situation. For example, NOTCH inhibitors such GSI (Gamma-Secretase Inhibitor) and MK-0752 for solid tumors have been tested in Phase I clinical trials, resulting in stable disease [ 42 , 43 ]. EMT and tumor cells’ invasiveness in various malignancies were also enhanced by collagen-rich CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overexpression of Notch signaling has been found to be associated with poor prognosis or poor response to treatment of some solid tumors [ 5 , 7 ]. Therefore, therapeutic strategies have first been developed in the preclinical phase and in early-phase clinical trials to target oncogenic functions of Notch in tumor cells [ 8 ]. Recent findings highlighted a central role for abnormal Notch in CRC and indicated a correlation between the overexpression of Notch signaling components and CRC progression and metastasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 E). The Notch signaling pathway is involved in various inflammatory diseases and cancers [ 16 , 17 ]. The KEGG pathway enrichment analysis showed that it was one of the most altered pathways.…”
Section: Resultsmentioning
confidence: 99%